Butyrate and Forskolin Augment Host Defense, Barrier Function, and Disease Resistance Without Eliciting Inflammation - Robinson, Kelsy; Yang, Qing; Li, Hong; Zhang, Long; Aylward, Bridget; Arsenault, Ryan J.; Zhang, Guolong (Frontiers in Nutrition, 2021)
Host defense peptides (HDPs) are an integral part of the innate immune system with both antimicrobial and immunomodulatory activities. Induction of endogenous HDP synthesis is being actively explored as an antibiotic-alternative approach to disease control and prevention. Butyrate, a short-chain fatty acid, and forskolin, a phytochemical, have been shown separately to induce HDP gene expression in human cells. Here, we investigated the ability of butyrate and forskolin to induce the expressions of chicken HDP genes and the genes involved in barrier function both in vitro and in vivo. We further evaluated their efficacy in protecting chickens from necrotic enteritis. Additionally, we profiled the transcriptome and global phosphorylation of chicken HD11 macrophage cells in response to butyrate and forskolin using RNA sequencing and a kinome peptide array, respectively. Our results showed a strong synergy between butyrate and forskolin in inducing the expressions of several, but not all, HDP genes. Importantly, dietary supplementation of butyrate and a forskolin-containing plant extract resulted in significant alleviation of intestinal lesions and the Clostridium perfringens colonization in a synergistic manner in a chicken model of necrotic enteritis. RNA sequencing revealed a preferential increase in HDP and barrier function genes with no induction of proinflammatory cytokines in response to butyrate and forskolin. The antiinflammatory and barrier protective properties of butyrate and forskolin were further confirmed by the kinome peptide array. Moreover, we demonstrated an involvement of inducible cAMP early repressor (ICER)-mediated negative feedback in HDP induction by butyrate and forskolin. Overall, these results highlight a potential for developing butyrate and forskolin, two natural products, as novel antibiotic alternatives to enhance intestinal health and disease resistance in poultry and other animals.